Reimplantation of an Anomalous Coronary Artery Arising from the Pulmonary Artery - Andrea Quarti; Alessandro D'Alfonso; Massimo Colaneri; Alessandra Baldinelli; Maria Grazia Bettuzzi; Marco Pozzi (Case Reports in Medicine)
A case of anomalous origin of the left coronary artery from the pulmonary artery in a patient with the origin of the coronary opposite to the aorta is reported. Between many surgical options we conclude to reestablish a double coronary system reconnecting the coronary through a conduit created with a pulmonary wall baffle and an autologous pericardial patch.